Glasswing‐Butterfly‐Inspired Multifunctional Scleral Lens and Smartphone Raman Spectrometer for Point‐of‐Care Tear Biomarker Analysis (Adv. Sci. 5/2023). Issue 5 (14th February 2023) - Narasimhan, Vinayak; Siddique, Radwanul Hasan; Kim, Un Jeong; Lee, Suyeon; Kim, Hyochul; Roh, YoungGeun; Wang, Yibing Michelle; Choo, Hyuck
Abstract : Bioinspired Nanostructures How can glasswing butterflies make contact lenses more functional? In article number 2205113, Radwanul Hasan Siddique, Hyuck Choo, and co‐workers have shown that integrating glasswing butterfly wing‐inspired nanostructures on a scleral lens can enhance visibility, block UV radiation, reduce bacterial infection and add sensing capabilities too! Such bioinspired scleral lens sensors can detect lysozyme and lactoferrin in whole human tears for chronic dry eye disease management.